2023
DOI: 10.3389/fncel.2023.1080344
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: Underlying mechanism and the crosstalk with other modes of neuronal death after intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a serious cerebrovascular disease with high rates of morbidity, mortality, and disability. Optimal treatment of ICH is a major clinical challenge, as the underlying mechanisms remain unclear. Ferroptosis, a newly identified form of non-apoptotic programmed cell death, is characterized by the iron-induced accumulation of lipid reactive oxygen species (ROS), leading to intracellular oxidative stress. Lipid ROS causes damage to nucleic acids, proteins, and cell membranes, eventua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Emerging evidence has shown that ferroptosis plays a role in the genesis of secondary brain injury after ICH (SBI-ICH). 19 , 304 328 Data revealing the roles of epigenetic regulation of ferroptosis by ncRNAs in ICH are limited. LncRNA H19 protects against ICH-related injuries by regulating the microRNA-106b-5p/ACSL4 axis.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 99%
“…Emerging evidence has shown that ferroptosis plays a role in the genesis of secondary brain injury after ICH (SBI-ICH). 19 , 304 328 Data revealing the roles of epigenetic regulation of ferroptosis by ncRNAs in ICH are limited. LncRNA H19 protects against ICH-related injuries by regulating the microRNA-106b-5p/ACSL4 axis.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 99%
“…Secondary brain injury following ICH includes neuronal death, ROS accumulation, and DNA damage. At present, neuronal death and ROS accumulation are two critical aspects requiring of comprehensive investigation after ICH 3,4 . Hence, further research is necessary to understand how hematomas and their decomposition products cause these two events following ICH.…”
Section: Introductionmentioning
confidence: 99%